2019
DOI: 10.1093/ckj/sfz163
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized cross-over study with objective quantification of the performance of an asymmetric triacetate and a polysulfone dialysis membrane using different anticoagulation strategies

Abstract: Background Different strategies can be used to counteract coagulation of extracorporeal systems. Systemic anticoagulation is most widely used in routine clinical practice, but can be contraindicated in specific settings. The Solacea™ dialyser, containing the asymmetric triacetate membrane, claims improved biocompatibility, which should result in decreased tendency for coagulation. We quantified the performance of the Solacea™ versus the FX800CORDIAX dialyser regarding resistance to fibre bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Apart from this thin layer, percentage open bers in the FX800 CorDiax were already lower after a 60min dialysis, and were, for 70% open ber area, further decreased by 66% (interval 60-240min) and 63% (interval 120-240min). These data con rm earlier work, in which it was demonstrated that better biocompatibility resulted in less activation of the coagulation cascade, even at very low levels of anticoagulation 3,5,9 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Apart from this thin layer, percentage open bers in the FX800 CorDiax were already lower after a 60min dialysis, and were, for 70% open ber area, further decreased by 66% (interval 60-240min) and 63% (interval 120-240min). These data con rm earlier work, in which it was demonstrated that better biocompatibility resulted in less activation of the coagulation cascade, even at very low levels of anticoagulation 3,5,9 .…”
Section: Discussionsupporting
confidence: 90%
“…Dialyzer extraction ratios for the middle molecules myoglobin and lambda and kappa free light chains, as measured at 1 hour after dialysis start, were not found associated with dialyzer ber patency post dialysis 3 . This absence of association suggests that ber blocking is a more delayed phenomenon that occurs only later in the dialysis session.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous research of our group using the gold standard of fiber quantification by micro-CT indicated that a substantial number of fibers can become blocked before this is reflected in a change of routinely observed dialysis parameters or in termination of the dialysis session 2 . We also demonstrated that type of dialyzer (more or less biocompatible), dose and type of anticoagulation strategy, and duration of the dialysis session, next to patient factors such as inflammation, impact substantially on the number of patent fibers at the end of the dialysis session 3 8 .…”
Section: Introductionmentioning
confidence: 86%